Analysis of Bio-briquette Electrical Energy from The Utilization of Combustion Ash in A Boiler Furnance (Ash Boilers) PKS PT. ADEI PLANTATION & INDUSTRY, MPOM - Prayetno, Tansyah; Jelita, Marhama (Program Studi Teknik Elektro Universitas Khairun, 2024)
PT. ADEI PLANTATION INDUSTRY is a palm oil processing factory that has a plantation area of 11,047 hectares. This factory produces solid and liquid waste. solid waste is reused as boiler fuel and liquid waste is used for biogas. Combustion in the boiler produces boiler ash, 70% of which is used as organic fertilizer and the remaining 30% is simply thrown away. This research aims to utilize boiler ash waste in bio-briquettes and determine the electrical energy potential of bio-briquettes using the carbonization combustion method in boiler furnaces (boiler ash). The test results for the calorific value of bio-briquettes from the use of residual ash from combustion in boiler furnaces (boiler ash) were 2,214.99 cal/gr. From 1 kg of boiler ash, 11 pieces of bio-briquettes weighing 100 gr/piece, with a calorific value of 24,364 cal/gr, are produced. PT. ADEI PLANTATION INDUSTRY in one day produce 7,536 tons of boiler ash, which will produce 82,896 pieces of bio-briquettes with a heating value of 179,903,776 cal/gr, a total flow rate of heat energy of 792,020 Watts and electrical energy of 950,424 kWh. From the PLTU efficiency of 5.12%, the potential electrical energy produced in one month is 28,512,720 kWh with 188.4 tons of boiler ash and 2,261 tons of boiler ash in 1 year has the potential to become 346,904,760 kWh of electricity. The electrical energy potential of bio-briquettes can meet the needs of 70% of the electricity load at PT. ADEI PLANTATION INDUSTRY, MPOM